Welke modellen voor de uitrol van publieke laadinfrastructuur voor elektrische voertuigen in het Brussels Hoofdstedelijk Gewest? - Quentin De Clerck; Lieselot Vanhaverbeke (Brussels Studies)
The impact of transport on climate change is becoming increasingly significant, making switching to sustainable vehicles an important step in emission reduction. The use of electric vehicles could be stimulated by a large network of charging stations. However, in Brussels, this network is still limited. In this paper, we propose two complementary methods that can support the deployment of a charging infrastructure. The analysis for public occasional charging is a point of interest (POI) based approach as it demonstrates that the accessibility of the charging infrastructure is improved if charging stations are installed at important Brussels mobility poles. Locations for public residential charging are identified by means of location models that take into account demand forecasts for EVs. The resulting roll-out is first pushed through where the estimated EV adoption is high and then spreads evenly across the entire Region. The combination of both methods offers a solution for residents (location models), as well as for visitors or commuters (POI approach).